Wandering son. Volume three - Shimura, Takako, 1973- (Fantagraphics Books, 2012)
"Shuichi and his friend Yoshino have a secret: Shuichi is a boy who wants to be a girl, and Yoshino is a girl who wants to be a boy. But one day, abruptly, their secret is exposed, and the two find themselves the target of sixth-grade cruelty. Their friendship is strained, as Yoshino makes a half-hearted effort at being a 'normal girl'-- and their mentor, Yuki, reveals the harder reality of being transgendered. Meanwhile, Shuichi's sister, Maho, realizes her dream of becoming a model, and drags Shuichi along for the ride. Shuichi meets another boy who wants to be a girl, and finds himself on an arranged date with a boy who doesn't know that the girl he has a crush on is actually a boy" -- from publisher's web site.